(untitled) (Baghdad Science Journal, 2025)
The erythrocyte aggregation is an important physiological phenomenon in the circulation of blood. It is a basic characteristic of normal blood that plays a major role in the cardiovascular system, especially in the microcirculation. This study explained the kinetics of single cells rouleaux formation one- dimensional aggregate and three- dimensional aggregate, during simultaneous, and the effect of hematocrit on the process of aggregation and sedimentation. The present study was done on forty one healthy subjects. Laser light is passed through a well mixed sample of blood and the forward scattered light intensities recorded continuously. The samples were prepared with different hematocrit, (10%, 15%, 20%, and 25%). Increasing the hematocrit, (10%, 15%, 20%, and 25%) had significantly decreased the rate of rouleaux formation (P< 0.005) but increase in the rate of one and three dimensional aggregate formation. On the other hand the sedimentation rate is decreased significantly (P